Technical and environmental assessment of sludge-derived slag generated from high temperature slagging co-gasification process as a sustainable construction material - Zhao, Ya (2024)
Tremendous amount of sludge is generated annually from freshwater treatment or sewage. The high temperature slagging co-gasification converts the sludge to slag showing the potential application for construction material. In this study, the physico-chemical properties of 4 types of slags generated from the co-gasification of municipal solid waste (MSW) with sludge from freshwater treatment or sewage, and ashes from sludge incineration are comprehensively analyzed. Leaching performance of the sludge-derived slag and mortar (with slag as the fine aggregate), as determined based on Toxicity Characteristic Leaching Procedure (TCLP), batch leaching and column leaching tests, indicates the slag can be considered safe for reutilization. Compressive strength test demonstrates that the mortars perform excellently and have the potential to replace sand in concrete production. The consolidation coefficient of slag (1.6 – 39.1 m2/year) is lower than the sandy silt but higher than clay. Additionally, the coefficient of permeability (∼1.96 × 10-3 m/s), angle of shearing resistance (∼39°), and undrained shear strength (375.5 ± 54.8 kPa) of the slag are comparable to sand. The life cycle assessment (LCA) is also conducted to evaluate the environmental impacts and benefits of reutilizing sludge-derived slag as an alternative material for concrete production and land reclamation.